Divine Exemplarity: Causality and Participation - Herrera, Juan José (Scripta Mediaevalia, 2024)
Thomas Aquinas explicitly affirmed a double divine exemplarity according to which the model of each thing is in God both in his intellect and in his nature. In the first case, the exemplars are the divine ideas; in the second, they are the divine attributes. Our work, discussing diverse contemporary Thomistic interpretations, attempts to explain the relationship between both dimensions of divine exemplarity and its consequences in the order of participation in the things created by God.